2016
DOI: 10.1080/10508619.2014.1003520
|View full text |Cite
|
Sign up to set email alerts
|

An Item Response Theory Analysis of The Questionnaire of God Representations

Abstract: The Dutch Questionnaire of God Representations (QGR) was investigated by means of item response theory (IRT) modeling in a clinical (n = 329) and a nonclinical sample (n = 792). Through a graded response model and IRT-based differential functioning techniques, detailed item-level analyses and information about measurement invariance between the clinical and nonclinical sample were obtained. On the basis of the results of the IRT analyses, a shortened version of the QGR (S-QGR) was constructed, consisting of 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Psychometric qualities of the questionnaire are adequate, and normative data are available for psychiatric patients and the general population and for persons who belong to different religious denominations (Schaap-Jonker & Eurelings-Bontekoe, 2009). A short version, which was constructed on the basis of Item Response Theory (IRT) analyses, is also available (Schaap-Jonker et al, 2016). In the current study, participants were instructed to indicate to which extent they experienced or recognized the feelings toward God and statements about God personally.…”
Section: Instrumentsmentioning
confidence: 99%
“…Psychometric qualities of the questionnaire are adequate, and normative data are available for psychiatric patients and the general population and for persons who belong to different religious denominations (Schaap-Jonker & Eurelings-Bontekoe, 2009). A short version, which was constructed on the basis of Item Response Theory (IRT) analyses, is also available (Schaap-Jonker et al, 2016). In the current study, participants were instructed to indicate to which extent they experienced or recognized the feelings toward God and statements about God personally.…”
Section: Instrumentsmentioning
confidence: 99%
“…It also exhibited an acceptable reliability level and displayed valid psychometrics. This validated questionnaire helped in collecting proper data for answering a research question [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not directly measure the extent to which participants in Experiment 1 actually held positive beliefs about God. Although prior work has shown that the population from which our sample was drawn (i.e., contemporary Christians in the Netherlands) generally has a highly positive God image (Schaap-Jonker et al, 2016), it is desirable to obtain more direct evidence for the role of God image. If the effects of prayer were driven by positive God beliefs and trust in God, as our theoretical analysis holds, we would expect the effects of prayer to be most pronounced among individuals who view God as a positive and trusting being.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in both experiments of the present research were contemporary Christians in the Netherlands. In a study among 792 self-identified Christians of varying ages, denominations, and societal backgrounds (Schaap-Jonker, Egberink, Braam, & Corveleyn, 2016), most participants reported a very positive God image. On a five-point scale, positive God image scores ranged from 3.59 to 4.39, whereas negative feelings towards God ranged from 1.4 to 2.5.…”
Section: The Present Research and Hypothesesmentioning
confidence: 99%